2001
DOI: 10.3748/wjg.v7.i3.376
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic potential of duodenal reflux juice from patients with long-standing postgastrectomy

Abstract: AIM To determine whether study on the carcinogenic potential of reflux juice from patients with remote gastrectomy could clarify the inherent relationship between duodenal reflux and gastric stump cancer. METHODS A total of 37 reflux juice samples (13 BillrothI, 24 BillrothII) were employed in the present study. A two-stage transformation assay using BALB/c 3T3 cells was carried out to test the initiating or promoting activity of these samples. RESULTS Two of 18 (11.1%) reflux samples exerted initiating activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Despite the fact that very little interest has been focused on a possible role of dietary carbonate in the development of gastric cancer, it is well recognised that this ion is a major constituent of the pancreaticoduodenal juice 39, 40. More importantly, this type of succus has been implicated as a mediator of reflux‐induced gastric cancer 35, 37, 41, 42, 43. In a recent study,11 we hypothesised that an elevated expression of ODC could be the molecular mechanism whereby carbonate increases the proliferation of gastric cells and the incidence of gastric cancer 11.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that very little interest has been focused on a possible role of dietary carbonate in the development of gastric cancer, it is well recognised that this ion is a major constituent of the pancreaticoduodenal juice 39, 40. More importantly, this type of succus has been implicated as a mediator of reflux‐induced gastric cancer 35, 37, 41, 42, 43. In a recent study,11 we hypothesised that an elevated expression of ODC could be the molecular mechanism whereby carbonate increases the proliferation of gastric cells and the incidence of gastric cancer 11.…”
Section: Discussionmentioning
confidence: 99%
“…There is a chance that some of the morphological changes of the residual mucosa were already present at surgery in relation to the causative disease and that, in the postoperative period, these lesions persisted, pro-gressed, and/or even regressed in relation to HP status [39][40][41][42][43] and undefined other multiple factors. 44 However, it was impossible for us to retrospectively ascertain the status of the gastric mucosa at the time of surgery. We observed that the prevalence of mucosal lesions in both groups was irregularly related to the time.…”
Section: Commentmentioning
confidence: 99%
“…[ 2 ] Chemotherapy and radiotherapy are used as adjuvant treatments for patients with T2, 3N in advanced or inoperable GC. [ 3 4 5 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%